2016
DOI: 10.1103/physrevb.93.184202
|View full text |Cite
|
Sign up to set email alerts
|

Metadynamical approach to the generation of amorphous structures: The case ofa-Si:H

Abstract: We present a dynamical approach to generate defect-free continuous-random-network (CRN) models of hydrogenated amorphous silicon (a-Si:H). Using the atomic co-ordination number of silicon as a collective variable and few configurational constraints, we have shown that classical metadynamics can be used to construct CRN models of a-Si with arbitrary concentrations of dangling-bond co-ordination defects. These defective networks have been subsequently hydrogenated to produce high-quality models of a-Si:H using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Alternatively, we can make use of assumptions about the anticipated geometric arrangements within the material to design empirical potentials, thus avoiding the computational expense of ab initio calculations 20,21 . These can be very effective for cases where we already understand the nature of the interactions within a material, although they still often require more sophisticated algorithms to produce the highest quality models 22,23 . For a-Si, one of the simplest and most successful approaches has been the Wooten Winer Weaire (WWW) algorithm, which generates four-fold coordinated random networks by combining bond-switch moves with relaxation against a classical potential 14,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, we can make use of assumptions about the anticipated geometric arrangements within the material to design empirical potentials, thus avoiding the computational expense of ab initio calculations 20,21 . These can be very effective for cases where we already understand the nature of the interactions within a material, although they still often require more sophisticated algorithms to produce the highest quality models 22,23 . For a-Si, one of the simplest and most successful approaches has been the Wooten Winer Weaire (WWW) algorithm, which generates four-fold coordinated random networks by combining bond-switch moves with relaxation against a classical potential 14,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Moreover, non-bonded hydrogens (NBHs) or unbonded hydrogens, most likely H 2 molecules, also exist in the voids, 15,[17][18][19][20][21] and occupying T-like sites. [21][22][23] It is known that bonded hydrogen content (C BH ) [24][25][26][27][28] and film thickness (d) 29) are related to the optical band gap (E opt ). Considering the relationship between E opt and the internal stress, it has been suggested that the incorporated divacancies and nanovoids induced anisotropic volumetric compressive stress in the a-Si network, resulting in an enhancement in E opt .…”
Section: Introductionmentioning
confidence: 99%
“…% H and an a-Si:D model with 12.2 at. % D. The models were generated using a recently developed metadynamical approach, 26 which is capable of producing high-quality networks of a-Si:H/D, 26 coupled with ab initio interactions. The CPMD simulations are based on the density-functional theory (DFT) of Kohn and Sham, 27,28 which employs norm-conserving pseudopotentials and plane-wave basis functions, as implemented within the NWCHEM code.…”
Section: Computational Methodologymentioning
confidence: 99%